Design of receding-horizon estimators for the battery assembly system. Issue 1 (July 2017) - Majdzik, Pawe; Witczak, Marcin; Seybold, Lothar; Witczak, Piotr
Abstract: The paper concerns the state estimation problem of a class of discrete-event systems. It is solved by defining a receding-horizon objective function that depends both on the prediction and output error. The system and its variables are described within the (max, +) algebra, which makes it possible to incorporate robustness within the overall framework. The paper also shows how to transform the interval cost function into the scalar one, and hence, making the computational procedure trackable within the quadratic programming framework. As a result, the proposed approach provided interval estimates of the system state, which can be used for both fault diagnosis and control purposes. An exemplary system is the battery assembly one, which is being designed and implemented in RAFI GmbH Company (one of the leading electronic manufacturing service providers in Germany). The final part of the paper shows illustrative examples, which exhibit the the performance of the proposed approach.